Fabrication and implementation of compact, low-power, three-dimensional, Cockcroft-Walton photomultiplier tube power supplies - Tompkins, Samuel James (Kansas State University, 2023)
A photomultiplier tube high-voltage power supply was constructed using a ”Free-Form” method of fabrication. The main goal of this project was to benchmark the performance of an experimental additive manufactured high-voltage power supply that is currently being investigated at Kansas State University. This is achieved through the comparison of non-traditional methods and material to traditional materials of the same circuit in a similar oriented geometry. A printed circuit board layout was considered to be insufficient for comparison due to the large differences in geometry compared to the 3-dimensional additive circuit. The method used to provide high-voltage and proper dynode stage biasing was a half-wave Cockcroft-Walton voltage multiplier. The 3-dimensional orientation was achieved through the Free-Form process with surface mount devices connected end-to-end or stacked together to form 3-dimensional shapes using temporary scaffolding and supports. This construction method used a low component-count design that was developed in an earlier phase of the project. The Free-Form method along with the previously designed circuit helped achieve a minimal package footprint while offering reliable biasing to the dynode stages. This work includes an in-depth description of the Free-Form construction methods used to produce the 3-dimensional circuit along with electrical characteristic testing, and spectral analysis results. A comparison for size and weight was made between the prototypes and the commercially available E11807-01 resistive divider base. A performance comparison was made using an external +5V supply for the prototypes and an external NHQ 103M high-voltage power supply for the E11807-01. The electrical characteristic measurements included dynode stage voltages, photocathode regulation, photocathode voltage stability, and power consumption. Spectral analysis was conducted using the following check sources, ¹³⁷Cs, ⁶⁰Co, and ²²Na. The prototypes and the E11807-01 were tested using a CsI(Na) crystal attached to an R11265U series photomultiplier tube. A total of two prototypes were produced using the Free-Form fabrication method. The final bulk dimensions for prototype A are 2.99 x 2.78 x 0.75 cm with a weight of 7.73g. Prototype B’s final bulk dimensions are 2.98 x 2.77 x 0.87 cm with a weight of 8.7g. The final dimensions of the additive manufactured printed experimental power supply that is being benchmarked are 2.99 x 2.77 x 0.65 cm with a weight of 8.36g. A 38.8% reduction in volume and a 34.7% reduction in weight was achieved through the Free-Form fabrication method when compared to the E11807-01 resistive divider. The photocathode voltage regulation values about its set point achieved for each prototype were +0.36% -0.60% for prototype A, +0.35% -0.83% for prototype B, and ±0.68% for the printed prototype. The maximum power consumption of each prototype while driving the photomultiplier tube were 53.41 mW for both prototype A and B and 69.53 mW for the printed prototype. The energy resolution’s measured for the full Cs-137 energy peak using a CsI(Na) crystal were 6.949% for prototype A, 7.851% for prototype B, 6.93% for the printed prototype, and 6.855% for the E11807-01.
Keywords: Low power; Compact circuit; Photomultiplier tube; High-voltage power supply; Cockcroft-Walton voltage multiplier; Spectroscopy